The Queer State of Being: Navigating the Neoliberal City through Kari - Nanjani Gandhi; S. Visaka Devi (IAFOR Journal of Cultural Studies, 2025)
Cities, marked by the strains of neoliberalism and neoconservatism, direct bodies in specific directions and orient themselves to regulate what counts as “good” and “poor.” While neoliberalism promotes individualism, neoconservatism is centered on conserving specific ways of life. The life of the social, impressed upon by these two strains, results in the process of embodiment vis-a-vis these influences. The city is mapped according to certain ideological frameworks, and it is difficult to feel at ease for bodies that do not subscribe to them. The current text analyses how urban spaces can foreclose themselves to queer people due to their inability to navigate life according to social norms. This paper endeavors to unravel the intricate dynamics between spatial exploration, feelings of estrangement, and the potential for reconnection within the neoliberal and neoconservative urban environments. It does so by a close reading of Amrutha Patil’s (2008) graphic novel Kari. Within the theoretical framework of phenomenology, the paper argues that after Kari’s engagement with the unproductive and unconventional spaces helps her reintegration into society as a more evolved version of herself. Focusing on Kari’s interactions with atypical spaces such as the sewers, dubious alleys, and the residence of an ill acquaintance/friend, the research aims to decipher how these locales amplify a sense of detachment from mainstream society, at the same time connecting her to the city. Rather than accepting alienation passively, the study looks at Kari’s engagement with such spaces.